Israel-Palestine War: The Right of Self-Defense in International Law - Qureshi, Tahir; Shah, Shaeyuq Ahmad; George, Sunil; Sapre, Abhilash Arun (Jurnal Cita Hukum, 2025)
This paper examines the use of force in self-defence under customary international law, focusing on the Israel-Palestine war. It analyses explicitly whether the attacks on 7 October 2023 by Harakat al-Muqawamah al-Islamiyyah (Hamas) and Palestinian Islamic Jihad (PIJ) can be construed within the parameters of Article 51 of the United Nations Charter as an "armed attack" justifying Israel’s use of military force in self-defence against non-state actors. The study employs a qualitative research method with a literature-based and legal approach, relying on analysing international treaties, customary international law principles, and relevant case law. The right to use force in self-defence in international and criminal law is discussed in the context of countering an armed attack or an imminent threat, aligning with the concept of jus ad bellum, which regulates the conditions under which states may initiate conflict. Furthermore, the paper emphasises that all forms of self-defence must comply with the Caroline principles, namely necessity and proportionality. Through a critical review of legal doctrines and international responses, this research seeks to provide a nuanced understanding of how traditional self-defence rights are applied to contemporary conflicts involving non-state actors. The findings underscore the complexities and evolving interpretations of self-defence in modern international law.